2012
DOI: 10.1200/jco.2012.30.34_suppl.260
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the effectiveness of a prechemotherapy teaching session: A Brown University Oncology Group study.

Abstract: 260 Background: Pre-chemotherapy teaching sessions, often coordinated by nursing personnel, are an opportunity to educate patients on treatment side effects, schedule, medications for toxicities such as nausea, and how to contact the oncology team if adverse events develop. Our institution provides a structured 60-minute nurse-coordinated pre-chemotherapy teaching session. The aims of this study were to evaluate whether pre-chemotherapy teaching sessions improve patient knowledge, preparedness, and anxiety in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Before initiating therapy, the patient is educated by a unique nurse education team, which provides information on the risks and benefits of radium-223 therapy, reviews treatment schedules and special precautions, and most importantly, answers patient-initiated questions about this first-in-class therapy. We have observed that nurse-guided treatment education reduces patient anxiety 8. The medical oncology team monitors the laboratory values before each treatment cycle and communicates with nuclear medicine in assessing the appropriateness of continuing therapy.…”
Section: The Genitourinary Multidisciplinary Clinicmentioning
confidence: 99%
See 1 more Smart Citation
“…Before initiating therapy, the patient is educated by a unique nurse education team, which provides information on the risks and benefits of radium-223 therapy, reviews treatment schedules and special precautions, and most importantly, answers patient-initiated questions about this first-in-class therapy. We have observed that nurse-guided treatment education reduces patient anxiety 8. The medical oncology team monitors the laboratory values before each treatment cycle and communicates with nuclear medicine in assessing the appropriateness of continuing therapy.…”
Section: The Genitourinary Multidisciplinary Clinicmentioning
confidence: 99%
“…We have observed that nurse-guided treatment education reduces patient anxiety. 8 The medical oncology team monitors the laboratory values before each treatment cycle and communicates with nuclear medicine in assessing the appropriateness of continuing therapy. Laboratory values are assessed before the initiation of radium-223 and before each subsequent cycle.…”
Section: The Genitourinary Multidisciplinary Clinicmentioning
confidence: 99%